Ozone microbubbles disinfection technique to inactivate penicillium digitatum in suspension - A. Chuajedton (2018)
This study investigated the effectiveness of ozone microbubbles on the growth inhibition of Penicillium digitatum at various reaction times. The iodine liberation and oxidation reduction potential (ORP) were directly used to measure the oxidation efficiency of ozone microbubbles generator. The iodine liberation and oxidation reduction potential (ORP) of ozone microbubbles treatments were rapidly increased with the highest rate within first 15 min. The spore suspension of P. digitatum was exposed to ozone gas and ozone microbubbles for 0, 15, 30, 45 and 60 min and incubated at 27°C for 48 h. Ozone microbubbles are demonstrated best result on the inactivation of P. digitatum spore germination. The percentage of spore germination significantly decreased after exposed to ozone microbubbles for 15 min, and completely inhibited the spore germination of fungus at 60 min. Furthermore, after treated with ozone microbubbles, abnormal spore was observed.